Enhancing local absorption patterns within gold nano - structures on a dielectric surface under an afm probe and with evanescent - wave illumination - Moghaddam, Sina Talebi. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
This study considers enhancing localized absorption by a gold nanoparticle (NP) placed over a substrate where an atomic force microscope (AFM) tip is in close proximity of the particle. The gold NP and AFM tip are interacting with a surface evanescent wave, resulting the near- eld coupling between the tip and NP and consequently enhances the absorption. This concept can be used for selective heating of NPs placed over a surface and is applicable when localized heating is desired for precise manufacturing at nanometer scales. Di erent tip positions are considered to identify the optimal tip location and the corresponding enhancement limits. The e ects of these interactions on the absorption pro les of dielectric core-shell NPs are also studied. It is observed that using core-shell nanoparticles with a dielectric core leads to further enhancement of the absorption e ciency and a more uniform distribution of absorption over the shell. Discrete dipole approximation coupled with surface interactions (DDA-SI) employed through the study, it is vectorized to improve its computational e ciency.
Keywords: Atomic force microscopy.